THE INFLUENCE OF LEARNING MOTIVATION ON ELEMENTARY SCHOOL STUDENTS' MATHEMATICS LEARNING OUTCOMES - Fitari, Nia (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
The purpose of this study is to determine the motivation level of students in class II SDN 05 Sagu, Galing District, as well as the connection between performance and mathematical study. The method is descriptive quantitative and uses a four-point Likert scale instrument questionnaire to examine three indicators: independence study, extrinsic motivation, and internal motivation. Using the entire sampling strategy, all 16 students were included in the sample. Descriptive and basic correlation statistics were used to analyze the data.According to research findings, motivation With the highest (average) score of 3.42 for intrinsic motivation, the study student falls into the medium high category. Mathematical achievement falls into the good (average) group as well (value 78). Motivation learning and accomplishment in mathematics are positively and significantly correlated (r = 0.61; p < 0.05), meaning that students with higher levels of motivation also have better learning outcomes. Results This demonstrates that enhancing intrinsic and extrinsic motivation, as well as bolstering autonomous learning, is crucial for supporting of learning mathematics at the school level.